2014
DOI: 10.1177/0731684414542992
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid green nanocomposites of poly(lactic acid) reinforced with banana fibre and nanoclay

Abstract: Green nanocomposites of poly(lactic acid)/banana fibre/nanoclay were successfully prepared using melt-blending technique followed by injection moulding. Untreated and chemically modified banana fibres and organically modified nanoclay (Cloisite 30B) were used as reinforcing agent within the poly(lactic acid) matrix. The banana fibres were subjected to various chemical modifications such as mercerization, silane treatment, sodium lauryl sulphate treatment, permanganate treatment and combination of mercerization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 49 publications
(83 reference statements)
4
22
0
Order By: Relevance
“…The volume fraction of fiber has been selected based on our previous findings. [16,23] Characterization FTIR analysis of the fiber, PLA and grafted samples (about 3 mg) was carried out using Thermo Nicolet6700 FTIR spectrometer, Thermofisher, USA. The FTIR spectra were recorded from 400 to 4000 cm À1 with 4 cm À1 resolution.…”
Section: Preparation Of Composites With and Without Gcmentioning
confidence: 99%
“…The volume fraction of fiber has been selected based on our previous findings. [16,23] Characterization FTIR analysis of the fiber, PLA and grafted samples (about 3 mg) was carried out using Thermo Nicolet6700 FTIR spectrometer, Thermofisher, USA. The FTIR spectra were recorded from 400 to 4000 cm À1 with 4 cm À1 resolution.…”
Section: Preparation Of Composites With and Without Gcmentioning
confidence: 99%
“…One of the most promising and cost‐effective polymers to produce bio‐nanocomposites is poly(lactic acid) or polylactide (PLA) reinforced with cellulose micro‐ or nanoparticles. Low toxicity as well as production and use‐related environmental compliance of PLA make it an ideal material for the manufacture of food packaging, scaffolds, wound coverings, etc …”
Section: Introductionmentioning
confidence: 99%
“…MACO/Jute composite exhibited a unique damping behavior at room temperature as well as at higher temperature. Silane-treated fibers and 3% C30B nano clay offered better strength and modulus due to formation of hydrogen bonds of nano clay between fibermatrix interfaces [11]. Srinivasan et.al [13] had observed that the tensile strength of Flax-Banana based GFRP composite is 39 N/mm 2 [19].…”
Section: Mechancial Characterizationmentioning
confidence: 99%